Health data managers’ perceptions and acceptance of health management information systems - Alhamoud, Mohammad Yahya; Sa’ad Ziyad, Khalid Saeed; Alharbi, Murad Salman (International journal of health sciences, 2019)
This study seeks to understand the concept of the acceptance and perceptions that these individuals have towards health management information systems, and how the resultant management is shaping this system. As a research area, health management information systems implementation challenges have been well studied, but little is known about the perceptions and acceptance of the individuals partially responsible for the successful implementation and management of health management information systems. Acceptance of health information systems in the workplace is a widely studied research area, and many factors that affect the acceptance of information technology have been quantified. However, to date, no research has focused specifically on understanding the acceptance levels of health data managers with regard to health management information systems. Health management information systems, if effective, enhance the delivery of patient-centered care, administrative efficiency, and the actual communication between healthcare professionals working within certain health sectors, and on a broader scale, cuts out the limbo of non-evidence-based practices.